Factors influencing the digitization process of Peruvian SMEs: management education, internationalization and business size - Afan Torres, Joaquin Marcel (2025)
Business digitalization plays a fundamental role in the success of micro, small and medium-sized enterprises (SMEs), being crucial for their competitiveness and sustainability. This study aims to identify the key factors that influence the digitalization process of Peruvian SMEs. The research was conducted using a quantitative approach, with a simple random sample of 271 SMEs located in Metropolitan Lima. A survey based on a five-point Likert scale was used, targeting heads, managers, administrators and/or owners of SMEs distributed across the five geographical regions of the city. The results, obtained using JAMOVI statistical software and a linear regression analysis, reveal that the education level of managers, the degree of internationalization and the size of the company are determining factors in the digitalization process. These findings highlight the importance of implementing strategies that promote adaptability to new technological trends to enhance business competitiveness. Finally, despite its limitations, this study provides a valuable starting point for future research in other sectors and contexts similar to the Peruvian business environment.